The Beiderbecke affair - Gallagher, William (London ; New York : Palgrave Macmillan on behalf of the British Film Institute, 2012)
With as little plot as its creator Alan Plater could get away with and as much jazz as he could manage, the 1985 television drama The Beiderbecke Affair had a far-reaching impact, inspiring sequels, novels, albums and even jazz tours. Much like its Bix Beiderbecke-style soundtrack, Plater's quietly joyous drama was unconventional, free: its narrative following the lives and relationships of its leading characters - teachers-turned-amateur detectives Trevor Chaplin (James Bolam) and Jill Swinburne (Barbara Flynn) - with a gentle, whimsical humour. William Gallagher's illuminating study is the first critical account of this much-loved series. Drawing on interviews with cast members and musicians, the production team and Yorkshire TV executives, as well as on insights from Plater himself, Gallagher explores Beiderbecke's origins in Plater's 1981 tv drama Get Lost! before moving on to an in-depth analysis of the series itself, to reveal why such an unassuming series remains one of the best-loved examples of British television drama. The book also includes a previously unpublished BBC Radio 4 short story featuring the character of Jill Swinburne, 'A Brief Encounter with Richard Wagner'"--Publisher's web site.
HKBU library
YT2025 M09